PERKEMBANGAN KONSEP PATOGENESIS ATEROSKLEROSIS - Lintong, Poppy (Jurnal Biomedik : JBM, 2009)
Abstract: Nowadays, the concept of the pathogenesis of atherosclerosis is called a response to injury hypothesis. This is based on the fact that atherosclerosis is a chronic inflammatory disease induced by endothelial injury (endothelial dysfunction). This chronic inflammatory disease consists of sequences of cellular and molecular responses, and is induced and accelerated mainly by endothelial injury. Furthermore, this injury causes compensatory responses which change the endothelial homeostasis, and increases the endothelial permeability and adhesion of leucocytes or platelets to endothelial cells. Many factors can trigger this endothelial injury, but the most important ones are haemodynamic imbalance and hypercholesterolemia. Besides these, vascular myocytes, together with extracellular matrix, play some significant roles in developing fatty streaks to become atheroma plaques. Key words: atherosclerosis, endothelial injury, lipid, chronic inflammation, vascular myocytes.     Abstrak: Konsep patogenesis aterosklerosis saat ini disebut hipotesis respons terha-dap cedera.  Konsep ini mengacu pada aterosklerosis sebagai penyakit radang kronik yang diinduksi oleh cedera endotel (disfungsi endotel). Proses radang kronik pada aterosklerosis terdiri dari rangkaian  respons seluler dan molekuler. Sebagai faktor utama yang dapat menginduksi dan memacu proses radang disini adalah cedera endotel. Adanya cedera endotel menyebabkan terjadinya respons kompensatorik yang mengubah homeostasis endotel serta meningkatkan permeabilitas endotel dan adhesi lekosit atau trombosit terhadap endotel. Banyak faktor dapat mencetuskan terjadinya cedera endotel namun yang terpenting adalah gangguan hemodinamik dan hiperkolesterolemia. Selain itu sel otot polos pembuluh darah juga turut berperan dalam aterogenesis yang bersama-sama dengan matriks ekstrasel mengubah fatty streak menjadi bercak ateroma. Kata kunci: aterosklerosis, cedera endotel, lemak, radang kronis, otot polos pembuluh darah.